-8y-6=9(y+5)

Simple and best practice solution for -8y-6=9(y+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8y-6=9(y+5) equation:


Simplifying
-8y + -6 = 9(y + 5)

Reorder the terms:
-6 + -8y = 9(y + 5)

Reorder the terms:
-6 + -8y = 9(5 + y)
-6 + -8y = (5 * 9 + y * 9)
-6 + -8y = (45 + 9y)

Solving
-6 + -8y = 45 + 9y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-9y' to each side of the equation.
-6 + -8y + -9y = 45 + 9y + -9y

Combine like terms: -8y + -9y = -17y
-6 + -17y = 45 + 9y + -9y

Combine like terms: 9y + -9y = 0
-6 + -17y = 45 + 0
-6 + -17y = 45

Add '6' to each side of the equation.
-6 + 6 + -17y = 45 + 6

Combine like terms: -6 + 6 = 0
0 + -17y = 45 + 6
-17y = 45 + 6

Combine like terms: 45 + 6 = 51
-17y = 51

Divide each side by '-17'.
y = -3

Simplifying
y = -3

See similar equations:

| 8(x+8)-2x=22 | | 3(v-6)+6v=-36 | | 30=6(w+3)-4w | | 7-6y=33 | | 20-6y=33 | | 10a-7=73 | | 10a-7=72 | | 10a-7=78 | | 10a-2=48 | | 5x+7x-2x= | | 3(3d-5)=2(d+8) | | 5x-4-4x-13=20 | | 3x+4=3x+10 | | t+14=34-37 | | -6(x-9)=-8x+44 | | x/((0.005-x)(2-4x)^4) | | 3/8+4/7= | | x+0.23x=258.30 | | x/((0.01-x)(4-4x)^4) | | 10+m=25 | | d-3=10 | | 43-4x=45*x-7 | | a+12=17 | | 2m(m-1)+3(1-m)=0 | | y=x^3-3x+2 | | 8e+9= | | 43-4x=45*x | | 43-4x=45*x/7 | | 43-4x=45*x^7 | | 12x^4-3x-2=0 | | 9+x*6=(14+x)*3 | | 100=3x^2+17x-20 |

Equations solver categories